Enzo Cucchi e Ettore Sottsass - Lacagnina, Salvatore (Milano : Charta, 2001)
To resist a world ever less willing to observe with care and with the heart, Enzo Cucchi and Ettore Sottsass, two subversives, two natural-born rebels, propose to us a dialogue inspired by a land they both love : Sicily. If Cucchi's immagination is close to the mythological feeling and the ritual sacrality in which Sicilian culture has been traditiionally rich. Sottsass has always derived vital inspiration for his works from Mediterranean colours alndscape and architecture. Cucchi and Sottsass met for the first time in 1999 on a common ground of reflection and vision. But in the dialogue they have since undertaken, each has always preserved his own clearly distinct character. This book documents the works they have realized together in two years of artistic partnership : the drawings, the projects, the sketches that have accompanied their dialogue until the mounting of the present exhibition in the Galleria Civica d'Arte Contemporanea Montevergini in Siracusa, where Sottsass has designed and built a structure to house two Greek sculptures of the 5th century BC and Cucchi has painted two large reed mats that hang gracefully from the ceiling.
Enzo Cucchi e Ettore Sottsass, Galleria Civica d'arte contemporanea Montevergini, Siracusa, 15.09. - 30.11.2001
Italiaanse titel, Italiaanse en Engelse tekst
boek
Keywords: Cucchi, Enzo; Sottsass, Ettore